How the current non‐significant effects of person‐centred care on nurses' outcomes could be abated by the WE‐CARE roadmap enablers: A discursive paper - Cornelia Van Diepen; Andreas Fors; Monica Bertilsson; Malin Axelsson; Inger Ekman; Gunnel Hensing (Nursing Open, 2023)
Abstract Aim To describe the non‐significant results in nurses' outcomes after the implementation of person‐centred care (PCC) and discuss if and how enablers of the WE‐CARE roadmap for implementing PCC could abate the non‐significant results. Design In this paper, an innovative framework of enablers in the WE‐CARE Roadmap is explained in relation to increased PCC and nurses' job satisfaction. Method Findings from a scoping review and published material provided how PCC and nurses' outcomes connect. The WE‐CARE roadmap entails five enablers: Information technology, Quality measures, Infrastructure, Incentive systems and contracting strategies. Results The WE‐CARE roadmap was described and each enabler in the WE‐CARE roadmap is discussed concerning PCC and the nurses' job satisfaction. Thus far, the effects of PCC on nurses' outcomes have been non‐significant. The WE‐CARE roadmap enablers can be implemented to ensure an increased PCC implementation and higher nurses' job satisfaction.